The effect of military base closures on young adults - David Sandberg (Lund University, School of Economics and Management, Department of Economics, 2024)
This study examines the response among young adults to the closure of a large local employer. By using military base closures in Sweden, I find that men experience lower earnings and enroll in tertiary education. This is driven by low-ability men who choose shortterm enrollment at nearby colleges and universities. For women, the closures have a positive impact after some years, with increases in both earnings and employment rates, suggesting that closing down a male-dominated employer can benefit the female labor supply.
Keywords: H56; I23; J24; 330; local economic downturn; plant closure; defense cutback; tertiary education; labor market entrants